Association between the clinical and histopathological classifications of actinic keratosis and the efficacy of topical imiquimod treatment. Issue 4 (19th December 2017) - Yu, Akitoshi; Tanizaki, Hideaki; Kokunai, Yasuhito; Kaneda, Kazuma; Sugimoto, Akira; Otsuka, Toshihiro; Kurokawa, Teruo; Moriwaki, Shinichi
Abstract: We investigated the association between the clinical and histopathological classifications of actinic keratosis (AK) and the efficacy of topical imiquimod treatment. Forty patients (55 lesions) with AK were treated with topical 5% imiquimod and the efficacy of imiquimod for AK was evaluated based on the clinical/histopathological changes. The complete remission (CR) rates in patients with the different clinical classifications of AK were 85.4% (erythematous type) and 46.2% (hyperkeratotic type). The CR rates in the different histopathological classifications of AK were 80% (hypertrophic type), 81.8% (atrophic type) and 42.9% (bowenoid type). The results revealed that determining the clinical and histopathological type of AK was important for selecting a therapeutic method. The topical imiquimod treatment could be expected to be more effective for AK clinically classified as the erythematous type, or histopathologically classified as the atrophic or hypertrophic type. However, it would be expected to be less effective for the treatment of AK clinically classified as the hyperkeratotic type or histopathologically classified as the bowenoid type. Our observations suggest that we can predict the efficacy of topical imiquimod therapy in AK by determining its clinical and histopathological type.